2012
DOI: 10.1590/s2176-94512012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Cementum, apical morphology and hypercementosis: a probable adaptive response of the periodontal support tissues and potential orthodontic implications

Abstract: Information about orthodontic movement of teeth with hypercementosis is scarce. As cementum deposition continues to occur, cementum is expected to change the shape of the root and apex over time, but this has not yet been demonstrated. Nor has it ever been established whether it increases or decreases the prevalence of root resorption during orthodontic treatment. The unique biological function of the interconnected network of cementocytes may play a role in orthodontic movement and its associated root resorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
(17 reference statements)
0
16
1
4
Order By: Relevance
“…Hypercementosis (increased cementum thickness) around the roots of the anterior teeth (Fig. S2C) indicates high masticatory/paramasticatory loads (44) and advanced age (49). Ensuing calcification and overload of the periodontal ligament (50) might have led to loss of periodontal hafting, which then caused the marked lingual "overtipping" of the incisors, concomitant root exposure on the labial side, and incipient resorption on the external bony plate of the symphysis.…”
Section: Resultsmentioning
confidence: 99%
“…Hypercementosis (increased cementum thickness) around the roots of the anterior teeth (Fig. S2C) indicates high masticatory/paramasticatory loads (44) and advanced age (49). Ensuing calcification and overload of the periodontal ligament (50) might have led to loss of periodontal hafting, which then caused the marked lingual "overtipping" of the incisors, concomitant root exposure on the labial side, and incipient resorption on the external bony plate of the symphysis.…”
Section: Resultsmentioning
confidence: 99%
“…Under rare conditions, cementum becomes thicker, referred to as hypercementosis, and this is characterized by the non-neoplastic hyperplasia of cementum and commonly occurs in the apical area of the involved tooth (11,24). However, hypercementosis is rare under general occlusal conditions although cementoblasts are mechanically stimulated.…”
mentioning
confidence: 99%
“…The incidence of hypercementosis by race or population group has not yet been established. The most frequently affected teeth are mandibular molar, followed by mandibular and maxillary second premolars and mandibular first premolars 4. However, some authors have found premolars to be the most commonly affected teeth 1 2…”
Section: Discussionmentioning
confidence: 99%